Penguatan peran warga masyarakat dalam mitigasi dan adaptasi menghadapi wabah Covid-19 di Kabupaten Kolaka - Sudarman Rahman; Sahidin Sahidin (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
WHO China Country Office reported pneumonia cases in Wuhan, Hubei Province, China. The virus was lately identified as a new strain of corona virus called Severe Acute Respiratory Syndrome Coronavirus-2. The new cases grow massively and became pandemic. Regarding this rapid transmission, there is a need for socialization to strengthen people’s awareness and role in mitigation and adaptation against this  COVID-19 pandemic. The method used was counseling with socialization or lectures and supported interactions in the form of questions and answers by using power points and leaflets/brochures as information media. This community engagement included the activities of the Movement for Healthy Living Society (GERMAS), Clean and Healthy Living Behavior (PHBS), Use of Personal Protective Equipment such as using masks, Use of Antiseptics and Disinfectants, and Planting Family Medicines (TOGA). The implementation of this activity began with socialization to the local community at the village hall, then to the houses of residents to deliver the subject contained in the brochure/leaflet, and last by placing pamphlets in public places to provide information to the community related to the activities that had been done. This socialization is expected to increase public awareness to face against this corona virus disease outbreak.